Angiogenesis, Inflammation, Platelets Count, and Metastatic Status as a Predictor for Thrombosis Risk in Nasopharyngeal Carcinoma Patients - Aru W Sudoyo; Andhika Rachman; Kuntjoro Harimurti (Acta Medica Indonesiana)
Aim: to assess the use of of angiogenesis, inflammation, platelets count, and metastatic status as predictors for thrombosis risk represented by soluble P-selectin level in nasopharyngeal carcinoma (NPC) patients. Methods: a cross sectional study was conducted on NPC patients at the Hematology and Oncology Clinic of Cipto Mangunkusumo Hospital, Jakarta, during Mei to October 2012. Data regarding angiogenesis (CD105 and VEGFR-2), inflammation (IL-6), platelets count, and metastatic status were assessed at enrollment, as well as soluble P-selectin levels in all eligible patients. Bivariate analysis continued with multiple linear regression analysis were done to identify independent predictors for soluble P-selectin levels. Results: sixty NPC patients were enrolled in the study. There was correlation between platelet counts (r=0.389; p=0.002), IL-6 (r=0.595; p<0.001) and number of metastatic sites (r=0.542; p<0.001) with soluble P-selectin level, and a linear regression analysis showed that these three variables can predict soluble P-selectin levels with adjusted R-square 65%. There was no correlation between VEGFR-2 and CD105 levels with soluble P-selectin levels.Conclusion: platelet counts, IL-6 level, and number of sites of metastasis can be used as predictors of soluble P-selectin level as parameter of thrombosis risk in NPC patients. Key words: nasopharyngeal carcinoma (NPC), thrombosis risk, soluble P-selectin.